UPAYA GURU KELAS DALAM MEMBANTU PESERTA DIDIK YANG MENGALAMI KESULITAN BELAJAR - Maulina, Yosita - (Bimbingan dan Konseling, 2014)
This research was based of the efforts that classroom teachers do in helping students whohave difficulties of learning in three basic capabilities: the ability to read, write and count. Thisresearch is a descriptive qualitative research that describing about the efforts of classroom teachers inhelping student who have difficullties in SD N 07 Padang Panjang. Key infomants 2, 3 and 4classroom teachers and additional informants were students who have difficulties, the instrumentsused in this research are interviews and documentation studies. Data analyze through data reduction,data display and conclusion. The results of this study indicate that the efforts in learning is to conductremedial teaching through specialized counseling conducted after school. Tutoring is done by using aspecial method that can facilitate learners in mastering a lesson is given.